The ovarian transcriptome of the cattle tick, Rhipicephalus (Boophilus) microplus, feeding upon a bovine host infected with Babesia bovis - Heekin, Andrew M (BioMed Central, 2013)
BACKGROUND: Cattle babesiosis is a tick-borne disease of cattle with the most severe form of the disease caused by the apicomplexan, Babesia bovis. Babesiosis is transmitted to cattle through the bite of infected cattle ticks of the genus Rhipicephalus. The most prevalent species is Rhipicephalus (Boophilus) microplus, which is distributed throughout the tropical and subtropical countries of the world. The transmission of B. bovis is transovarian and a previous study of the R. microplus ovarian proteome identified several R. microplus proteins that were differentially expressed in response to infection. Through various approaches, we studied the reaction of the R. microplus ovarian transcriptome in response to infection by B. bovis. METHODS: A group of ticks were allowed to feed on a B. bovis-infected splenectomized calf while a second group fed on an uninfected splenectomized control calf. RNA was purified from dissected adult female ovaries of both infected and uninfected ticks and a subtracted B. bovis-infected cDNA library was synthesized, subtracting with the uninfected ovarian RNA. Four thousand ESTs were sequenced from the ovary subtracted library and annotated. RESULTS: The subtracted library dataset assembled into 727 unique contigs and 2,161 singletons for a total of 2,888 unigenes, Microarray experiments designed to detect B. bovis-induced gene expression changes indicated at least 15 transcripts were expressed at a higher level in ovaries from ticks feeding upon the B. bovis-infected calf as compared with ovaries from ticks feeding on an uninfected calf. We did not detect any transcripts from these microarray experiments that were expressed at a lower level in the infected ovaries compared with the uninfected ovaries. Using the technique called serial analysis of gene expression, 41 ovarian transcripts from infected ticks were differentially expressed when compared with transcripts of controls. CONCLUSION: Collectively, our experimental approaches provide the first comprehensive profile of the R. microplus ovarian transcriptome responding to infection by B. bovis. This dataset should prove useful in molecular studies of host-pathogen interactions between this tick and its apicomplexan parasite.